Effect of berberine on pentylenetetrazol-induced seizures in rats - Hamid Reza Sadeghnia; Sahar Darbarpanah; Seyed Mahmood Hosseini (Mashhad University of Medical Sciences, 2011)
Objective: Antiepileptic drugs (AEDs) that are usually used for treatment of epilepsy have substantial side effects and about 30% of patients continue to have seizures with current AEDs therapy. Some herbs which traditionally used in the management of seizures of many rural areas of the developing countries have shown anticonvulsant activity in modern pharmacological bioassays. The aim of the present study was to evaluate the effects of berberine, an alkaloid from Berberis vulgaris, on seizures induced by pentylenetetrazol (PTZ) in rats. Material and Methods: Rats (n=6-7) received berberine (100, 200 and 400 mg/kg, i.p.), diazepam (4mg/kg, i.p. as positive control), and vehicle (saline) and then 30 min later PTZ (110mg/kg, i.p.) were injected . Behavioral responses of the animals to PTZ administration were evaluated using these criteria: latency to first minimal clonic seizure (MCS), incidence of MCS, latency to the first generalized tonic-clonic seizures (GTCS), incidence of GTCS, protection against GTCS and mortality. Results: Intraperitoneal administration of lower doses of berberine (100 and 200 mg/kg) had no significant effects on minimal clonic seizures (MCS) and generalized tonic-clonic seizures (GTCS) latencies, while injection of 400 mg/kg caused significant increase in both MCS and GTCS latencies (p